Factors influencing patients' engagement with ChatGPT for accessing health-related information - Fahad Alanezi (Taylor & Francis Group, 2024)
This study aims to investigate the factors influencing patients' engagement with ChatGPT for accessing health-related information. A quasi-experimental design with a mixed-methods approach including both quantitative online survey and qualitative interviews was adopted in this study for data collection and analysis. A total of 139 and 24 outpatients were recruited for survey and interviews, respectively. Twenty-eight influencing factors were identified from both survey and interview analysis that may affect positively or negatively on patients' engagement on ChatGPT. Survey results revealed user-centric factors, including perceived usefulness (mean score rating = 3.59), followed by trustworthiness (Mean score rating = 3.53) to be major influencing factors, while interview findings revealed ChatGPT-related factors such as information quality, ethical concerns, and technical limitations as the major influencing factors. ChatGPT has exponentially generated users' interest in its features and functionalities, but there are still some concerns which may limit their engagement. Areas of future research include ChatGPT and patient satisfaction; ChatGPT for public health awareness; and ChatGPT for self-management of chronic diseases.